PENGEMBANGAN DAYA TARIK WISATA BUDAYA DESA SLANGIT, CIREBON, JAWA BARAT - Altri Tiyar Barunawati; Syamsul Alam Paturusi (Magister Tourism Study, Faculty of Tourism, Udayana University, 2016)
Slangit is a village in Cirebon, West Java that has potentials to be used as a cultural tourist attraction. These potentials include tradition and custom ceremonies, traditional art of masks and mask performances. This article investigates the the development strategy of cultural attractions in the village of Slangit. Data collection are conducted by observation, in-depth interviews, and documentation. Data was analysed using a descriptive qualitative method and by using SWOT analysis. The result shows that theattempt to use arts potential as tourist attraction has been fairly developed by artists group but it is far from adequate becausethe lack of coordination between artists group and the authorityresponsible to promote culture and tourism. It is suggested thatthe government to work together with communities and artists topromote the village potentials as cultural tourism attractions bothas away to preserve arts and to develop tourism as source of localeconomy.